Control of the hematopoietic stem cell state - Knapp, David JHF; Eaves, Connie J (Cell research, 2014)
Several studies have demonstrated the clonal transmission of distinct differentiation and self-renewal properties in hematopoietic stem cells during the regeneration of blood production in transplanted recipients. A recent publication now identifies Vwf expression as a discriminating marker of a hematopoietic stem cell state that is primed for platelet production in response to thrombopoietin, but also subject to developmental and other, as yet undefined, cues.